EFFICACITY EVALUATION OF SOME ANTI-DRIFT AGENTS IN THE CONDITIONS OF CARACAL PLAIN, ROMANIA - Gheorghe MATEI; Cătălin Viorel POPESCU; Mirela PARASCHIVU; Călin SĂLCEANU; Elena ROȘCULETE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The increasing use of pesticides in modern agriculture has led to increased concerns about the risk of pollution of surface waters, soil and its agro-productive properties. The application of large doses of pesticides using outdated technologies and non-performing agricultural equipments, with poor application in terms of distribution uniformity and the lack of farmers’ knowledge and measures to prevent the drift phenomenon leads to their spread outside the targeted areas and implicitly to the increase of environmental pollution. In the present study, three anti-drift agents: EM260 (dodecilbenzensulfonat of calcium 50%, and butanol 18%), SC (heptametiltrisiloxan polietilenglicol) and respectively SO (surfactant non – ionic) have been tested according to ISO 22866, in the field conditions of Agricultural Research Development Station (ARDS) Caracal, Romania. The obtained results emphasized that the most valuable, among all variants, was EM260 (dodecilbenzensulfonat of calcium 50%, and butanol 18%) with smaller drift effect recorded at 1 meter distance (6.4%), followed by the second point, at 3 meters (3.1%) and at 5 meters with a calculated value of 2.1%. Also, at this variant the affected plants percent was smallest from the entire tested assortment, of 35.2%.